010 Inspiring compassionate care in an acute hospital setting – the power of QELCA. (1st October 2013) - Standfield, Robert; Wellings, Val; Harrison, Alison; Garside, Jennifer
Abstract : Transforming the traditional delivery of specialist end-of-life care education and training for nursing staff in acute hospital settings through the Quality End of Life Care for All (QELCA) education and training programme has resulted in immediate positive benefits for both the hospice and the local acute hospital Trust. The prevalence of a top-down target driven culture has meant that persuading hospital managers in hospital settings that compassionate care is directly relevant to improving acute care has been a challenge. The opportunity to transform this thinking was taken by the local acute hospital when they embarked on the Transforming End of Life Care in Acute Hospitals Programme that includes the adoption of the AMBER care bundle and incorporates QELCA training. Through the delivery of the prescribed QELCA curriculum, that combines and integrates theory with experiential learning through working alongside experienced hospice nurses, there has been a transformational change in the nursing care. This is underpinned by changed thinking and delivery of care that focuses directly on the needs of the patient rather than the needs of the organisation. The impact in the Acute trust has included: 82% of relatives said they were aware that their relative's recovery was uncertain. 91% of patients received care supported by the AMBER care bundle had a patient and family meeting. 1.5% of patients who received care supported by the AMBER care bundle, who were discharged were admitted back to the hospital in an emergency. 100% patients had a DNACPR Form completed. Successful partnership working has also resulted in a renewed interest in furthering specialist palliative and end-of-life care education within secondary care and the CCG extending the AMBER care bundle/QELCA as part of their CQUIN investment. Further funding for the QELCA training has been provided through a successful bid to the Strategic Health Authority.